1980
DOI: 10.1021/bi00555a015
|View full text |Cite
|
Sign up to set email alerts
|

Location of the heme groups in cytochrome cd1 oxidase from Pseudomonas aeruginosa

Abstract: The disposition of the heme groups in cytochrome cd1 oxidase from Pseudomonas aeruginosa is studied by emission spectroscopy. This protein of molecular weight 120 000 is composed of two monomers each with a heme c and a heme d1. It has been shown by electron microscopy to be oblong in shape and by preliminary X-ray crystallography to have a twofold axis of rotation. Three electronic energy donors, a singlet tryptophan, a triplet tryptophan, and an attached 8-dimethylamino-1-naphthalenesulfonyl group, all exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The presence of mutually unfavourable interactions between the two sites binding reduced cytochrome c-551 may tentatively be correlated to the limited structural information available on cytochrome oxidase, which is a symmetrical dimer where both the haem c pair and the haem d pair are located close to each other (Takano et al, 1979). Moreover, fluorescence energy-transfer experiments have indicated that the four haem groups are segregated at one extreme of the dimeric structure and that two large protein domains in the dimer are quite distant from the active site (Mitra & Bershon, 1980). It is not at all unreasonable, therefore, to assume that binding of a reduced cytochrome c-55 1 molecule to one of the two subunits of the dimer may limit, by steric hindrance and/or electrostatic effects, binding to the other subunit.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of mutually unfavourable interactions between the two sites binding reduced cytochrome c-551 may tentatively be correlated to the limited structural information available on cytochrome oxidase, which is a symmetrical dimer where both the haem c pair and the haem d pair are located close to each other (Takano et al, 1979). Moreover, fluorescence energy-transfer experiments have indicated that the four haem groups are segregated at one extreme of the dimeric structure and that two large protein domains in the dimer are quite distant from the active site (Mitra & Bershon, 1980). It is not at all unreasonable, therefore, to assume that binding of a reduced cytochrome c-55 1 molecule to one of the two subunits of the dimer may limit, by steric hindrance and/or electrostatic effects, binding to the other subunit.…”
Section: Discussionmentioning
confidence: 90%
“…Alcaligenes azurin was prepared at 40C by the procedure used for preparing respiratory chain proteins from P. aeruginosa (14) …”
Section: Methodsmentioning
confidence: 99%
“…A definite role for azurin has yet to be established (Henry & Bessiers, 1984). Azurins will react rapidly with cytochrome c-551 and with cytochrome cd, the soluble dimeric terminal oxidase (Gorin et al, 1983; Mitra & Bersohn, 1980;Silvestrini et al, 1981;Takano et al, 1979; Ugurbil et al, 1985). We have chosen to study holoand apoazurins of Pseudomonas aeruginosa (azurin Pae),1 Alcali genes faecalis (azurin Afe), and Alcaligenes denitrificans (azurin Ade).…”
mentioning
confidence: 99%